1978
DOI: 10.1029/ja083ia02p00599
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale characteristics of field‐aligned currents associated with substorms

Abstract: Characteristics of field-aligned currents have been determined during a large number of substorms from the magnetic field observations acquired with the Triad satellite. The statistical features of field-aligned currents include the following: (1) The large-scale regions of field-aligned currents determined previously by the authors (Iijima and Potemra, 1976a) persist during all phases of substorm activity, namely, region 1, located near the poleward boundary of the field-aligned current region, and region 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

74
511
3
6

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 865 publications
(594 citation statements)
references
References 48 publications
(34 reference statements)
74
511
3
6
Order By: Relevance
“…It is a region characterized by an exponential decrease of electron energy density with decreasing radial distance and is generally located at geocentric distances of ~6 to 8 RE in the nightside. It is implicitly assumed by a number of researchers that the inner edge of the plasma sheet is associated with an earthward decrease of the total plasma pressure and theories on the closure of the large scale region 2 field-aligned current system [lijima and Potemra, 1978] have been built upon this assumption (see, e.g., the review by Mauk and Zanetti, 1987). As pointed out by Mauk and Zanetti [1987], the observed plasma pressure shows a persistent earthward increase rather than a decrease in the geocentric distances usually ascribed to be the inner edge of the plasma sheet.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is a region characterized by an exponential decrease of electron energy density with decreasing radial distance and is generally located at geocentric distances of ~6 to 8 RE in the nightside. It is implicitly assumed by a number of researchers that the inner edge of the plasma sheet is associated with an earthward decrease of the total plasma pressure and theories on the closure of the large scale region 2 field-aligned current system [lijima and Potemra, 1978] have been built upon this assumption (see, e.g., the review by Mauk and Zanetti, 1987). As pointed out by Mauk and Zanetti [1987], the observed plasma pressure shows a persistent earthward increase rather than a decrease in the geocentric distances usually ascribed to be the inner edge of the plasma sheet.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Interestingly, there are two auroral regions that show the least seasonal variations in the energy of precipitating electrons. These regions, one in the dusk sector but equatorward of the oval and one in the dawn sector but poleward of the oval, approximately map to the statistical laxge-scale downward field-aligned currents [Iijima and Potemra, 1978]. It is likely that auroras seen in these regions are associated with ion precipitation, which is less affected by field-aligned potential drops.…”
Section: Uvi Imager and Data Preparationmentioning
confidence: 91%
“…With the advance in our knowledge about magnetosphere, the electrodynamics relation between the solar wind, magnetosphere and ionosphere are realized through the field-aligned currents. As was shown by Iigima and Potemra (1978), the field-aligned currents are closely connected with the auroral electrojets and the disturbance polar (DP) systems. They also showed that the location and intensity of the FAC are defined by the B z and B y components of the IMF.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous works present the experimental and theoretical relations found by their authors between the solar wind parameters and auroral ionosphere. The studies of Zmuda and Armstrong (1974), Iigima and Potemra (1978), Foster et al (1989) and other authors lead to the conclusion that the field-aligned currents (FAC) constitute a major interconnection between the magnetosphere and polar ionosphere. Intensive ionospheric currents during geomagnetic storms and disturbances can change the quiet ionosphere parameters.…”
Section: Discussionmentioning
confidence: 99%